The View from Saturn : Poems - Friman, Alice (Book collections on Project MUSE., 2014)
The View from Saturn endeavors to look at the earth and our life on it from two perspectives at once: objectively, as if from a great distance, and subjectively, focusing in on the body with all its cells and hungers. Alice Friman's poems dance between these two vantage points, asking the important questions: What does it all mean, and what have we become, standing in the midst of the destruction we've wrought by "watching the unthinkable going on"' With dark humor and lyric honesty, The View from Saturn provides both a telescopic and microscopic look at ourselves, exploring how in our smallness and perhaps foolishness we are still capable of attaining a measure of nobility.